الفتوى في القران الكريم -دراسة موضوعية - عقيب, نوال; شينون, حورية; بوته, مباركة (University of Eloued-جامعة الوادي, 2022)
"الحمد لله رب العالمين والصلاة والسلام على خاتم الأنبياء والمرسلين نبينا محمد وآله وأصحابه وبعد: تتمحور هذه الدراسة حول موضوع ""الفتوى في القرآن الكريم - دراسة موضوعية""؛ حيث قمنا بدراسة موضوع الفتوى في القرآن الكريم دراسة موضوعية، وتتبع ألفاظه ومعانيه وسياقاته، وحيث كانت الإشكالية الرئيسة في درستنا: ما هي أهم السياقات والدلالات والمفاهيم لمصطلح الفتوى في القرآن الكريم؟ وقمنا بالإجابة على هذا الإشكال: في مقدمة وثلاثة مباحث وخاتمة. أما المبحث الأول: فقد تضمن على الدراسة المصطلحية للفتوى. وأما المبحث الثاني: وقد تناول الفتوى وخطورتها ودورها في تحقيق استقرار المجتمع وأما المبحث الثالث: فقد اشتمل على أنواع السياقات التي وردت فيها الفتوى. وفي الأخير تطرقنا إلى خاتمة: اشتملت على أهم النتائج والتوصيات ومن أهم النتائج: 1- إن الفتوى هي طريق الحفاظ على خلود الشريعة، واستمراريتها، وصلاحيتها لكل زمان ومكان، لذلك وجب أن تكون صادرة ممن هو عالم بالنصوص الشرعية وبمدلولاتها. "˗ Praise be to God, Lord of the Worlds, and prayers and peace be upon the last of the Prophets and Messengers, our Prophet Muhammad and his family and his companions: ˗ The focus of this study is on the topic of “Fatwa in the Holy Qur’an – an objective study,” whereby we studied the subject of Fatwa in the Holy Qur’an an objective study, tracing its meanings and contexts, and where the main problem in our study was: What are the most important contexts, connotations and concepts of the term Fatwa in the Holy Qur’an? We answered this problem: in an introduction. As for the first topic: it included the terminological study of the fatwa. As for the second study: ˗ It included the doctrinal and legal connotations of the term fatwa. As for the third topic: it included the types of contexts in which the fatwa was mentioned. Finally, we touched on a conclusion: it included the most important results and recommendations, and the most important results are: Three sections and a conclusion. - The fatwa is the way to preserve the immortality of the Sharia, its continuity, and its validity for every time and place, so it must be issued by someone who is familiar with the legal texts and their implications.
مذكرة ماستر
Keywords: الفتوى - القران الكريم.; Fatwa - the Holy Quran.